(untitled) (Brazilian Journal of Research in Science Education, 2025)
This research aims to investigate the extent to which technoscience research relates to environmental racism within the scope of Scientific and Technological Education in the context of Latin America. Methodologically, we carried out a bibliographic survey in the Redalyc and Scielo databases, from 2002 to 2024. To analyze the identified works, we used ATD, from which two categories emerged: (i) Hegemonic technoscience and possible consequences for environmental racism in Latin America; (ii) Scientific and Technological Education, highlighting hegemonic technoscience and its consequences for environmental racism in Latin America. Among the results, we highlight the need to discuss the relationship between technoscience and environmental racism, within the scope of Scientific and Technological Education, in Latin America, to form critical subjects and overcome this problem.